2017
DOI: 10.7554/elife.22593
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 contributes to angiogenesis and chemotherapy resistance in glioblastoma

Abstract: Caspase-8 is a key player in extrinsic apoptosis and its activity is often downregulated in cancer. However, human Caspase-8 expression is retained in some tumors, including glioblastoma (GBM), suggesting that it may support cancer growth in these contexts. GBM, the most aggressive of the gliomas, is characterized by extensive angiogenesis and by an inflammatory microenvironment that support its development and resistance to therapies. We have recently shown that Caspase-8 sustains neoplastic transformation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 32 publications
1
51
1
Order By: Relevance
“…Similarly, drug-resistant ovarian cancer cells can also secrete more CCL2 and blocking CCL2 increased sensitivity of ovarian cancer cells to chemotherapeutic drugs 16 . Enhanced the expression and secretion of CCL2 also lead to neovascularization and increased resistance to chemotherapy in glioblastoma 43 . Indeed, we succeeded in detecting increased level of CCL2 in cancer patients before surgical tumor removal.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, drug-resistant ovarian cancer cells can also secrete more CCL2 and blocking CCL2 increased sensitivity of ovarian cancer cells to chemotherapeutic drugs 16 . Enhanced the expression and secretion of CCL2 also lead to neovascularization and increased resistance to chemotherapy in glioblastoma 43 . Indeed, we succeeded in detecting increased level of CCL2 in cancer patients before surgical tumor removal.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of caspase-8 may affect chemotherapy sensitivity not only by interfering with the apoptotic response, but also by additional pathways. Negative regulation of caspase-8 in GBM may trigger resistance to apoptosis, correlates with a reduction in the level of expression of inflammatory cytokines, resulting in increased sensitivity to TMZ via a yet unknown molecular pathway (Fianco et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Caspase-8 in GBM is often withdrawn, and is upregulated in a mesenchymal group (Verhaak et al, 2010;Stupack, 2013). But the silencing of Caspase-8 can sensitize the cancer cells with the use of the TMZ in the treatment (Fianco et al, 2016;Fianco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Fianco et al [ 20 ], using in vitro and in vivo glioblastoma models, highlighted the link between inflammation, angiogenesis and chemoresistance. The authors showed that in an inflammatory microenvironment, Caspase 8, a protein implicated in apoptosis, promotes NF-κB transcription factor activation with consequent increase of VEGF, IL-6, IL-8, IL-1β and MCP-1 secretion, enhancing neovascularization and resistance to temozolomide (TMZ), an alkylating agent widely used in glioblastoma treatment.…”
Section: Chemoresistance Due To Changes In Tmementioning
confidence: 99%